Hubungan Tingkat Pengetahuan Tentang Kesehatan Gigi Dengan Perilaku Perawatan Gigi Pada Anak Kelas 4-6 Di MI Al-Mubarokah Jakarta Selatan - Susilawati; Suri, Oryza Intan; Hasmiati , Titi (STIKes IMC Bintaro, 2023)
Background: Dental Health problems as; dental caries is an infectious disease caused by demineralization of enamel and dentin. According to WHO dental caries incidence in children has an increase of 60-90% in in grades 4-6. One of the factors that affects the dental caries are knowledge and awareness of importance dental health care. Objective: to determine the relationship between knowledge levels of dental health with dental care behavior in grades 4-6. Method: Type of analytic research with a cross-sectional approach. The population in this research 75 children. The sample technique in this study (tatal population). Data analysis used Chi-square test. Results: showed that respondents with a good knowledge showed positive behavior (65,2%), and the respondent with sufficient level of knowledge showed negative behavior (88,9%) and showed showed positive behavior (11,1%) and the responden wit a lack of knowledge showed negative behavior (88,9%). Statical test result obtained p value: 0,000 (<0,005). Conclusion: that there is a significant relationship on the knowledge levels of dental health with dental care behavior